A responsabilidade de proteger: possível resposta para o dilema da intervenção humanitária: The Responsibility to Protect: possible answer to the dilemma of Humanitarian Intervention - Silva, Bárbara Thaís Pinheiro (2023)
The purpose of the article is to analyze the Responsibility to Protect as a possible response to the dilemma of humanitarian intervention considering the precepts set out in the United Nations Charter. To this end, the concepts of sovereignty and non-use of force delimited in the Charter will be addressed, as these intrinsically imply the possible application of R2P or not. Subsequently, the objective is to present R2P from its genesis to the delimitation of its scope of application based on its legal contour; and, finally, the final considerations about the viability of R2P, as a possible response to the dilemma of humanitarian interventions. From this perspective, this article will use the hypothetical deductive method, in addition to bibliographical research and documentary analysis to develop a study with primacy.